Factors that influence the calculation of acoustic scattering by the method of source simulation - P.H. T. ZANNIN (Archives of Acoustics)
In this work the source simulation technique was used to calculate the scattering of a plane wave by a cylinder with radial or elliptical transverse section. The basic idea of the source simulation technique is to replace the scattering (or radiating) body with a system of simple sources located within the envelope of the scatterer (or radiator). The extent to which the simulated field reproduces the original one depends on the degree of correspondence between the simulated and the given boundary conditions. Numerical simulations have shown that: 1) the shape of the auxiliary surface; 2) the number of sources, and 3) the way the sources are distributed are the most relevant parameters to ensure an accurate solution of the problem. In the case of the single-layer method, the sources should not be positioned close to the surface or to the center of the body, because the problem becomes ill-conditioned. The auxiliary surface and the scatterer should be as similar as possible in order to minimize the boundary error. With respect to the number of sources (N), there are two opposite effects: 1) if (N) is too small, the sound field is not reproduced accurately; 2) if (N is too large, the computing time increases and the solution accuracy decreases. The method breaks down when the excitation frequency coincides with the eigenfrequencies - a narrow range of frequencies - of the space formed by the auxiliary surface. As the auxiliary surface is frequently represented by simple surfaces (cylinder, sphere), one can easily calculate the eigenfrequencies and therefore avoid them.